Unified Modelling Language (UML) dalam Perancangan Sistem Pendukung Keputusan Group Discussion Berbasis WEB - Akhi Ha Runi Nur Rahayu; Bait Syaiful Rijal (Gorontalo State University, 2023)
The discussion method is a technique for enhancing active student participation in the learning process. Challenges in the field often involve difficulties in determining group allocations for discussions. Considerations regarding students' intellectual domains can be used as a reference for determining discussion group allocations. Based on these issues, research needs to be conducted with the aim of designing and developing a decision support system application related to the problem of forming discussion groups. This system is constructed using Unified Modeling Language (UML) modeling. Modeling with UML can be useful for visualizing or modeling a system that will provide more detailed information in the design of a program. The end result of this research is a Web-Based Decision Support System for Discussion Group Allocations.